2007
DOI: 10.1007/s10729-007-9041-8
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to outliers in meta-analysis

Abstract: The synthesis of evidence from trials and medical studies using meta-analysis is essential for Evidence Based Medicine. However, problematical outlying results often occur even under the random-effects model. We propose a model that allows a long-tailed distribution for the random effect, which removes the necessity for an arbitrary decision to include or exclude outliers. In this approach, they are included, but with a reduced weight. We also introduce a modification of the forest plot to show the downweighti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 21 publications
2
85
0
Order By: Relevance
“…Rabiee et al (2004Rabiee et al ( , 2005 used this method in exploring sources of heterogeneity in the controlled internal drug-releasing insert (CIDR) and Ovsynch data. Baker and Jackson (2008) have proposed a method that reduces the weight of studies that are outliers in meta-analyses. All of these methods for examining heterogeneity have merit, and the variety of methods available reflects the importance of this activity.…”
Section: Approaches To Heterogeneitymentioning
confidence: 99%
“…Rabiee et al (2004Rabiee et al ( , 2005 used this method in exploring sources of heterogeneity in the controlled internal drug-releasing insert (CIDR) and Ovsynch data. Baker and Jackson (2008) have proposed a method that reduces the weight of studies that are outliers in meta-analyses. All of these methods for examining heterogeneity have merit, and the variety of methods available reflects the importance of this activity.…”
Section: Approaches To Heterogeneitymentioning
confidence: 99%
“…The two data sets: CDP-choline for cognitive and behavioural disturbances, and Fluoride toothpaste for preventing dental caries have been previously analysed [4]. These provide contrasting examples.…”
Section: Resultsmentioning
confidence: 99%
“…Excluding trial results based on their findings is another source of bias however and the presence of unexplained and unusual study results places the statistician in an uncomfortable situation. Outliers in regression analysis have been widely researched [2,3], but research into outliers in meta-analysis is much more recent [4,5]. If any outliers contribute very little weight to the analysis, because the studies that provide them are small for example, the choice between their inclusion or exclusion is moot; 'outlier' is not synonymous with 'influential'.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity analyses have also been used to examine the effects of studies identified as being aberrant concerning conduct or result, or being highly influential in the analysis. Recently, another method has been proposed that reduces the weight of studies that are outliers in meta-analyses 45 . All of these methods for examining heterogeneity have merit, and the variety of methods available reflects the importance of this activity.…”
Section: Negative Values Of Imentioning
confidence: 99%